Analisis Laju Pertumbuhan Kota Pematang Siantar dengan Menggunakan Konsep Integral Tak Wajar pada Tahun 2024–2025 - Suvriadi Panggabean; Petra Putri Sarinah Pandiangan; Mhd Fachrizal; Arief Rachman Pakpahan; Alya Dwi Lestari; Livia Mutianda; Lestari Novianti Sinurat (Lembaga Pengembangan Kinerja Dosen, 2025)
In this study, the population growth rate of Pematang Siantar City during the period 2022–2025 is discussed through an improper integral approach. Population growth patterns must be analyzed and predicted in the long term. Linear, geometric, and exponential growth models are used to analyze data taken from the Statistics Center. The calculation results show that the population growth rate changes every year, with an average change of 0.10% per year. The prediction for 2025–2026 shows a growth of 0.59%, indicating an increase in population. However, through an improper integral approach, it is found that a population that experiences a decrease in growth rate over time will reach a limited cumulative total population value, even if the population continues to increase. These results indicate that a long-term downward trend can lead to population shrinkage, uncontrolled growth can lead to population density. As a result, this study is expected to provide a scientific basis for population policies and sustainable development planning in Pematang Siantar City.